1993
DOI: 10.1007/bf00312625
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal part of the CDC25 gene product has Ras-nucleotide exchange activity when present in a chimeric SDC25-CDC25 protein

Abstract: The CDC25 gene from S. cerevisiae encodes an activator of Ras proteins. The C-terminal part of a structurally-related protein encoded by the SDC25 gene is characterised by a Ras-guanine nucleotide exchange activity in vitro whereas the C-terminal part of CDC25 gives no detectable exchange activity. A chimera between the 3' regions of these two genes was constructed by homeologous recombination. This chimeric gene suppresses cdc25 mutations. When expressed in E. coli, the chimeric product is detectable by antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It should be stressed that the gene nomenclature is arbitrary at this stage, because we have no evidence for a second RAS gene in Y. lipolytica or for a YlSDC25 paralog. In S. cerevisiae, Cdc25p is an essential GDP/GTP exchange factor (GEF) for Ras2 (8). CDC25 null mutants are lethal in S. cerevisiae, but homozygous CDC25 deletion mutants are viable in C. albicans, although the strains have a partial defect in hyphal formation (19).…”
Section: Discussionmentioning
confidence: 99%
“…It should be stressed that the gene nomenclature is arbitrary at this stage, because we have no evidence for a second RAS gene in Y. lipolytica or for a YlSDC25 paralog. In S. cerevisiae, Cdc25p is an essential GDP/GTP exchange factor (GEF) for Ras2 (8). CDC25 null mutants are lethal in S. cerevisiae, but homozygous CDC25 deletion mutants are viable in C. albicans, although the strains have a partial defect in hyphal formation (19).…”
Section: Discussionmentioning
confidence: 99%
“…The constructions are such that the lacZ gene is out of frame by −1 and +1 nucleotide in constructions pKB‐3TG and pKB‐3CG, allowing +1 and −1 frameshift mutations to be scored on indicator plates, respectively. The β‐galactosidase activity in lacZ + revertant yeast colonies is detected by overlaying yeast plates with X‐gal‐containing agarose (Boy‐Marcotte et al ., 1993). Plasmids isolated from independent colonies were sequenced and found to contain +1T or −1C frameshift events for pKB‐3TG and pKB‐3CG, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…When transfected into mammalian cells, it activates a Ras-dependent pathway (Rey et al, 1991), overcomes the dominant negative phenotype of H-rasN17 (Schweighoffer et al, 1993), and acts as an oncogene (Barlat et al, 1993a). The ability to make chimeric genes between the 3' part of CDC25 and SDC25 that encode active chimeric GEF on Ras was suggestive of a close relationship between the two genes (Boy-Marcotte et al, 1993). Nevertheless, the role of the complete SDC25 gene as a GEF for Ras in yeast was questionable because the deletion of SDC25 leads to no detectable phenotype, and the over-present in mammals (CDC25 Mm, Ras-GRF, and HGRF) has been found by structural and functional homology with Cdc25p.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrate that the wild-type gene SDC25 on a multicopy plasmid is able to functionally replace CDC25 with the same efficiency. The similarity between SDC25 and CDC25 at the nucleotide level allowed us to use homologous recombination as already described (Mezard et al, 1992;Boy-Marcotte et al, 1993) to construct two chimeric genes between SDC25 and CDC25 as shown on Figure 3. In the plasmid pCS1 the 5' part of CDC25 (codons 1 to 1031) has been fused to the 3' part of SDC25 (codons 704 to 1253).…”
Section: Sdc25 and Cdc25 Genes Are Under Different Transcriptional Rementioning
confidence: 99%